2021
DOI: 10.1007/s10646-021-02444-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sublethal concentrations of the antiparasitic ivermectin on the polychaeta species Hediste diversicolor: biochemical and behavioral responses

Abstract: Pharmaceutical drugs have emerged as major micropollutants in aquatic ecosystems. Their presence has been systematically reported in monitoring survey, and their wide distribution and constant presence in the wild is a direct consequence of their massive use, in both human and veterinary therapeutics. Drugs used to treat parasitic infections in livestock are major contaminants, given the amounts in which they are administered, and reach the aquatic compartment in high amounts, where they may affect non target … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Studies suggested that pesticides, antibiotics and heavy metals can trigger oxidative stress and induce antioxidant responses (Nunes et al, 2021;Sule et al, 2022;Wang et al, 2020). Other useful biomarkers indicative of neurotoxicity and neuroprotection are the activities of cholinesterases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested that pesticides, antibiotics and heavy metals can trigger oxidative stress and induce antioxidant responses (Nunes et al, 2021;Sule et al, 2022;Wang et al, 2020). Other useful biomarkers indicative of neurotoxicity and neuroprotection are the activities of cholinesterases.…”
Section: Introductionmentioning
confidence: 99%